PERILAKU PSK TERHADAP PENGGUNAAN KONDOM DALAM UPAYA PENCEGAHAN HIV/AIDS DI PERUM JONDUL LAMA KOTA PEKANBARU TAHUN 2017 - Zulmeliza Rasyid; Leon Candra; Kurniawan Saputra (LPPM Universitas Abdurrab, 2019)
Condom use is a person's behavior in using condoms to prevent pregnancy and illnesses such as HIV / AIDS. Data of Riau Province Health Office shows Pekanbaru City every year contributed the biggest HIV / AIDS case from 1997-2015 that is 894 cases of HIV and 833 AIDS cases, this is because there are still prostitutes who do not use condom during sexual intercourse. The purpose of this research is to know the behavior of PSK with knowledge, attitude, availability of condom, pimping support, health officer role to condom use in HIV / AIDS prevention effort at Perum Jondul Lama Pekanbaru City Year 2017. This research method is quantitative analytic cross sectional design. The sample of this study were 93 people. The sampling technique is saturated samling. The analysis used is univariate and bivariate analysis with Chi-Square test, measuring instrument used is questionnaire and data processing using computerization. The result showed that there was a correlation between knowledge Ï value 0,000, POR value = 9,146 (3,531-23,690), attitude Ï value 0,000, POR value = 30,694 (9,818-95,962), condom availability Ï value 0,000, POR value = 8,929 (3,386-23,545) , pimp support Ï value 0,000, POR value = 6,888 (2,728-17,390), health officer role Ï value, 0.001, POR value = 5,046 (2,057-12,379) Against condom use behavior. It is suggested to pimps to make mandatory rules to use condoms to both sex workers and their clients, so that the incidence of HIV / AIDS can be minimized